A transição agroecológica no assentamento rural Fazenda Pirituba: percepções, práticas e perspectivas - Narezi, Gabriela (Universidade Federal de São Carlos, 2008)
The importance of agroecologic transition for the agricultural nesting in the agrarian reform it s as an alternative front to the economic situation, in the recovery of degraded areas, the balance of agroecosystems and the viability of alimentary agricultural production to attend the needs of the families. The objective of this research was to analyze the agroecologic transition in the agricultural nesting Pirituba farm, in the cities of Itapeva and Itaberá, SP. The used methodology was the research-action and bibliographies. In the field work participative methodologies and half-structuralized interviews had been used. Five groups of agroecologic experimentation, the pointers of sustainability and the phases of each experimental agroecologic transition was identified and analyzed. It was shown that some families had interest in proceed in the agroecologic transition and that some areas demonstrated potential for agroecologic production. However, the continuity of these practices is compromised by some factors representing challenges for the families and also for the public policy of sustainable agricultural development. This work presents the perceptions, practice and perspective for the agroecologic transition in the agricultural nesting Pirituba Farm. Universidade Federal de Minas Gerais A importância da proposta da transição agroecológica no contexto dos assentamentos rurais se encontra na possibilidade da alternativa frente à atual situação econômica, na recuperação de áreas degradadas, na busca pelo equilíbrio dos agroecossistemas e na viabilidade de produção agrícola para atender as demandas alimentares das próprias famílias assentadas. Dessa forma, o objetivo desta pesquisa foi analisar a questão da transição agroecológica no assentamento rural Fazenda Pirituba, nos municípios de Itapeva e Itaberá (SP). O arcabouço metodológico foi baseado na pesquisa ação e em levantamentos bibliográficos. Foram utilizadas metodologias participativas e entrevistas semi-estruturadas para coleta de dados na área do ...